The last passenger - Finch, Charles (Charles B.) (Finch, Charles (Charles B.) Charles Lenox series, 2020)
"From bestselling author Charles Finch comes the third and final in a prequel trilogy to his lauded Charles Lenox series. London, 1855: A young and eager Charles Lenox faces his toughest case yet: a murder without a single clue. Slumped in a first-class car at Paddington Station is the body of a young, handsome gentleman. He has no luggage, empty pockets, and no sign of violence upon his person - yet Lenox knows instantly that it's not a natural death. Pursuing the investigation against the wishes of Scotland Yard, the detective encounters every obstacle London in 1855 has to offer, from obstinate royalty to class prejudice to the intense grief of his closest friend. Written in Charles Finch's unmistakably warm, witty, and winning voice, The Last Passenger is a cunning and deeply satisfying conclusion to the journey begun in The Woman in the Water and The Vanishing Man"--